PENDIDIKAN KELUARGA MUSLIM DALAM PERSPEKTIF FIQIH AL-QUR`AN - Kris Setyaningsih; Nurlaeli Nurlaeli; Mardeli Mardeli (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
Family as the smallest social unit in society is first and foremost a cultural environment in order to embed norms and develop habits and considered important for personal life, family and society. Key to the success of education in the family is actually located on spiritual education with a person's religious sense. Some things that play an important role in shaping a person's outlook on life include the supervision faith, morals, creativity they have. Medium is the Family Education is education that must be implemented in the family by parents to themselves, other family members and to his children. Family education can be interpreted as the actions and measures taken by the parent as the primary educator in the form of assistance, guidance, counseling and teaching to themselves, other family members and to their children, according to their potential each, with the effect either through interaction between them. So that members of the family and of the child can someday live independently in charge and it can be justified in the public sphere in accordance with the values of the prevailing culture, and religion. Therefore to find out more details of how the views of the Koran concerning family education, the author tries to do a more in-depth study of the Qur'anic perspectives on family education. Some of the Prophet described by the Qur'an as the head of the household. So it becomes a lesson and example to our families. Kata Kunci: Pendidikan, Keluarga Muslim, Fiqih Al-Qur’an